Prototype Deployment Of Examination And Quiz System (EQs) With Outcome Based Education In Networking System - Hidayah, Rahmalan; Zaheera, Zainal Abidin; Zuraida, Abal Abas; Ahmad Fadzli Nizam, Abdul Rahman; Abdul Samad, Shibghatullah; Ong, Rhui Yong (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This study focuses on deploying an evaluation system for lecturer to provide assessment document question sets such as final examination paper which is based on the outcome-based-education (OBE) approach. Using the OBE approach, student’s level of understanding, skill and cognition is set to align with learning outcomes (LO) and program outcomes (PO). However, in preparing the assessment as such the final examination, lecturers may tend to forget making an alignment with the LO and PO. In current practice, most lecturers preparing the final examination document find that it was quite tedious and challenging making sets of questions to align with the LO and PO. Thus, they need to consider the suitability of marks given according to the level of difficulties of those questions. As a result, in each semester, lecturers need to provide documents of examination questions papers, the examination answer scheme and the table of specification test. All these documents were provided manually and some of them did not manage to prepare the required documents properly. Thus, a prototype of Examination and Quiz System (EQs) with Outcomes-Based-Education is proposed. The objectives of this research are two folds: a) to propose an automated examination document that align with the LO and PO; b) to generate an automated Table of Specification Test based on the automated examination document. The impact of the new approach giving an innovative perspective in education world, which time allocation for preparing final examination questions is reduced and the question set is aligned with LO and PO.